A new minute species of Suphisellus Crotch, 1873 (Coleoptera: Noteridae) from South America, with new records and notes on other species of the genus - Urcola, Juan I.; Fery, Hans; Michat, Mariano C. (Zootaxa, 2026)
Suphisellus cucuminoi sp. nov. from Argentina is described and illustrated in detail. Externally, the new species is similar to S. hieroglyphicus Zimmermann, 1921, but can be readily distinguished by: (1) its smaller size, (2) a less convex dorsal body shape, and (3) the shape of the male genitalia. The first reliable record of S. hieroglyphicus from Argentina is provided, along with a brief diagnosis and the designation of a lectotype. Notes on Suphisellus flavopictus (Régimbart, 1889) are also provided. Suphisellus minimus Gschwendtner, 1922 is treated as a species inquirenda.